L’écriture à l’université : un outil pour conceptualiser - Philippe Clauzard (Éducation et Socialisation)
Our contribution examines the effects of Writing activity in Training Programs for adults, and more specifically the effects of Reflexive Writing with we call the "learning journal". These ones consist in productions for oneself, which are also addressed to the trainer's evaluation. Following Crinon (2000), we think that the work writings of work invite to thinking, learning and self-building. Writing is thus a tool for the development of thought, relating to both the objects of knowledge and the contents of the course. The object of our study is to demonstrate how these writings favor some raisings in abstraction, generalization and transfers into a transitional area of conceptualization, by allowing a conceptual elaboration, but also a secondarization of objects (Bautier, 2005). Writing at the university informs the teacher such as the student of their scopes of progress, by the first one’s performance and the other’s learning, finally stimulating a reflexive posture.